Kvalita výuky fyziky - případy začínajících učitelů - Vojtěch Žák; Jana Martínková (Karolinum Press, 2018)
The strategic goal of the research, including this empirical study, is to contribute to the search for the teaching quality and to deepen the understanding of the context of the teaching quality. The research questions were posed as follows: What are the quality parameters that are typical of teaching of selected novice teachers of physics? Which factors influence the teaching quality of the selected teachers? To answer these questions, a mixed method research design was used. A case study was chosen as the basic research plan. An ex-post facto research was chosen as the design of the quantitative part of the research, and the data was collected using the method of pedagogical observation. Regarding the qualitative part, the data was gained using semi-structured interviews. The research sample consisted of four novice physics teachers, teaching in Czech grammar schools. The presented research describes and uncovers the quality of their teaching. The study revealed that some of the observed parameters were fulfilled in a similar way regarding the particular teachers, for example the frequency and quality of the realized lecturing, the use of mathematical means, or no use of the heuristic method. The teaching process differed, for instance, in the frequency of conducting experiments, the work with text, or the support of the active learning of the pupils. Several domain-specific, domain-general and other factors influencing the teaching quality were identified. This research shows that it is reasonable to look at the teaching quality from a wider perspective.